Genetic control of the aluminum resistance trait in barley hybrids - O. V. Yakovleva (Труды по прикладной ботанике, генетике и селекции)
Background. Barley is a crop that reacts sharply to increased soil acidity. In acidic soil, free Al3+ cations are the most toxic. The negative effects of aluminum are especially pronounced in the early stages of plant development and with a lack of nutrients. The character of aluminum resistance is determined by the expression of oligogenes or polygenic complexes, as well as their interaction. The patterns of inheritance of aluminum resistance in barley have not been studied enough.Materials and methods. The material for the study included spring barley accessions contrasting in their resistance to toxic aluminum ions: highly resistant local accession k-9730 (Russia), and susceptible cv. ‘Colsess IV’. Phenotypically homogeneous lines were selected for hybridological analysis, and F1–F5 and F2BC1 hybrids were obtained. Segregation among hybrid populations in resistance was assessed according to the degree of growth of the aboveground part and root system under ion stress conditions at a testing concentration of 185 μ of aluminum ions and a pH level of 4.0.Results. High resistance of k-9730 barley plants to toxic aluminum ions, assessed by the responses of the root and sprout to the effects of the stressor, is controlled by two dominant genes. By selecting plants of older hybrid generations, valuable genotypes with high levels of resistance to ion stress were identified and a donor of aluminum resistance for barley, L-30-1, was developed, which is also characterized by other traits valuable for breeding.Conclusion. Studying the inheritance of resistance to toxic aluminum ions (185 μ Al3+, pH 4.0) in the k-9730 and ‘Colsess IV’ barley genotypes helped to establish a number of patterns. The results of the study are recommended to be used in the breeding process when choosing parent pairs to develop new barley cultivars that will be most adapted to adverse environmental conditions.